Efficacy and safety of viva QS capsule for nicotine addiction in Malaysian adult smokers - Mohamad Noor, Zaswiza; Nik Mohamed, Mohamad Haniki; Md Aris, Mohd Aznan; Draman, Samsul; Shaikh Rahman Bux, Siti Halimah Bux (2010)
We conducted a randomised, double-blind, placebo-controlled study to evaluate the effectiveness of Viva QS® capsule, a supplement consisting of twelve herbs, for the management of nicotine addiction. Smokers meeting study criteria were recruited into the study. Follow-up was undertaken for 6 months, with three assessment time points for smoking status andwithdrawal symptoms. Brief counseling was provided at each follow-up via telephone call at week 4 and 12. At week 24, face-to-face follow-up was done and self-reported abstinence was validated by measuring expired carbon monoxide level and cotinine in urine and/or saliva samples. Result: Of 155 smokers recruited, mean age was 35.2 ± 8.36 years. Mean baseline Fagerström test for nicotine dependence (FTND) score was 5.03 ± 1.39. 7-days point prevalence quit rate was 22.4% at week 24 [Viva QS = 30.7% vs. placebo = 13.9%]; p = 0.015; OR = 2.74 (CI =1.197-6.282), 34.7% at week 12 [42.7% vs. 26.2%; p = 0.038, OR = 2.08 (CI = 1.04-4.16) and 24.5% at week 12 [32% vs. 16.7%]; p =0.031; OR = 2.35 (CI = 1.07-5.17). Most common adverse events reported were sore throat (Viva QS =28.8% vs. placebo = 36.6%), dry mouth (17.8% vs. 16.9%) and cough (11% vs. 8.4%) There were no significant differences in all adverse events reported by subjects in both groups. Conclusion: Viva QS ® at least doubled smoking cessation rate vs. placebo in smokers with moderate to high level ofnicotine dependence without any significant adverse effects.